Analysis of SCOR Model Implementation for Green Supply Chain Management Performance Measurement: Case Study of PT. Bali Towerindo Sentra Tbk in the Fiber-to-the-Home (FTTH) Internet Service Industry - Nurcahyadi, Dedy; Sugiyono, Sugiyono (IJOSMAS, 2025)
This research analyzes the implementation of the Supply Chain Operations Reference (SCOR) Model within the framework of Green Supply Chain Management (GSCM) at PT. Bali Towerindo Sentra Tbk, specifically for their Fiber to the Home (FTTH) services. The aim is to measure supply chain performance by considering environmental aspects, operational efficiency, and customer satisfaction. A quantitative approach is used, employing a survey method with internal and external respondents, supported by primary data through questionnaires and interviews, as well as secondary data from company reports. Performance measurement uses the five key dimensions of SCOR: reliability, responsiveness, agility, cost, and asset management, aligned with GSCM indicators such as waste reduction, energy efficiency, and the use of environmentally friendly technologies. The analysis shows that the implementation of GSCM through the SCOR Model improves process efficiency, accelerates response to market demand, and reduces environmental impact. The findings provide strategic implications for the telecommunications industry, particularly in building a sustainable and adaptive supply chain to meet digital challenges. The integrative application of SCOR-GSCM has proven relevant for enhancing competitiveness, complying with environmental regulations, and strengthening the company's image among customers and stakeholders.